Grouting Design of Rich Water Tunnels and the Calculation of Distance between Annular Blind Pipes - Helin Fu; Pengtao An; Kai Li; Guowen Cheng; Jie Li; Xiaohui Yu (Advances in Civil Engineering)
The rich water tunnel often uses “water blocking and drainage limiting” waterproofing and drainage systems. On the one hand, the drainage system is set behind the lining to reduce the water pressure. On the other hand, the stratum grouting is used to control the discharge flow of groundwater. In the drainage system, it is important to determine the distance between the annular blind pipes, but there is no clear calculation formula, which leads to the designer often relying on experience. First, the groundwater drainage system is constructed. Based on Darcy’s law and the law of conservation of mass, the formula for calculating the seepage discharge and the seepage pressure with the parameters of annular blind pipe spacing is derived. At the same time, the design parameters of the grouting circle are optimised, and then the formula of annular blind pipe spacing is derived according to the design value of the antiwater pressure of the secondary lining structure and the allowable seepage discharge of the tunnel. Finally, based on the case study of the Hongtu extra-long tunnel under construction, it is verified by field monitoring data. The results show that (1) grouting reinforcement is an important means to reduce water seepage, and tunnel water seepage can be adjusted by changing the thickness and permeability coefficient of the grouting reinforcement circle, in which the thickness of the reinforcement circle should not be too large, and the permeability coefficient should not be less than 1/80 of the surrounding rock permeability coefficient; (2) according to the derived formula, the water pressure of the secondary lining structure decreases in a parabolic manner from the middle of the two rows of annular blind pipes to the place where the annular blind pipes are set; (3) the allowable water seepage of the tunnel and the design value of the water pressure resistance of the lining structure should be considered when determining the distance between annular blind pipes; and (4) based on the derived formula, the distance between the annular blind pipes in the test section of the Hongtu extra-long tunnel is determined to be 8 m.